(untitled) (Tempo e Argumento, 2011)
The article discusses how to reflect on history, memory and preservation of cultural property from the contact with cultural heritage in educational visits. We presuppose that the subjects in situations of educational present and offer new directions for cultural heritage. The visitors create narratives, where they explain their choices, confronting speeches and lectures from experts, collections, objects and historiographical visions.